Estimating the health economic impact of the universal varicella vaccination in Argentina from 2015 to 2019 - Norberto Giglio; Pieralessandro Lasalvia; Manjiri Pawaskar; Cintia I. Parellada; Diego Rosselli; Virginia V. Babic; Silvina E. Neyro (Human Vaccines & Immunotherapeutics, 2023)
Since the introduction of Universal Varicella Vaccination (UVV) in the Argentinean National Immunization Program in 2015, a significant decline in the incidence of varicella has been reported. This study aimed to estimate the economic impact of single-dose UVV in Argentina from 2015 to 2019. The economic impact was assessed based on the observed incidence of varicella in the post-UVV period and the number of cases avoided, obtained from a previously published study that used an Autoregressive Integrated Moving Average (ARIMA) model. The weighted average cost per case was calculated using local studies. The post-UVV cost reductions were calculated by multiplying the number of cases avoided from 2015 –2019 by the weighted average cost per case. Data were summarized yearly and by peak (September−November) periods for the target (1−4 years) and overall populations. We estimated avoided costs of United States dollars (USD) $65 million in the target population and $112 million in the overall population over 4 years following UVV introduction. We observed a trend toward greater reductions in costs over time, with substantial differences observed in peak periods. We estimated that the single-dose UVV program considerably reduced the economic burden of varicella in Argentina by avoiding direct and indirect costs associated with varicella management.